¿A quiénes afecta el desempleo? Análisis de la tasa de incidencia en Colombia (2009)
The incidence rate represents a composite indicator that takes account of both the number of unemployed people and the average duration of employments The analysis of this rate allows to portrait a more complete profile of those individuals who are more likely to either become unemployed or stay in such a situation. We find sire-leant differences in the analysis of the unemployment rate and the incidence rate in Colombia, which suggests the importance of addressing certain elements underlying unemployment duration when appraising unemployment bpology and policies aimed to overcome it.